The imperial premiership the role of the modern prime minister in foreign policy making, 1964-2015 - Goodman, Sam. (Manchester Manchester University Press, 2016)
Recent votes in the House of Commons on British military intervention have put foreign policy at the heart of public consciousness. This book examines fifty years and nine premierships - from Harold Wilson to David Cameron - to offer a unique account of the growing role of the prime minister in foreign policy making. The prime minister now spends more time on foreign policy than at any previous period outside war, but excepting crises the public and MPs themselves remain relatively ill-informed on the subject. Written by a senior parliamentary researcher and based on first-hand interviews with former foreign secretaries, Cabinet ministers, senior civil servants, party officials, military chiefs and diplomats, this book provides an insider account of votes on military intervention in Syria, and raises questions around the vetting of those who seek the office of prime minister and the educating of the electorate.
Includes bibliographical references and index.
Keywords: Prime ministers--Great Britain